A low-carbohydrate high-fat diet decreases lean mass and impairs cardiac function in pair-fed female C57BL/6J mice. Issue 1 (December 2016) - Nilsson, Jessica; Ericsson, Madelene; Joibari, Masoumeh; Anderson, Fredrick; Carlsson, Leif; Nilsson, Stefan; Sjödin, Anna; Burén, Jonas
Abstract Background Excess body fat is a major health issue and a risk factor for the development of numerous chronic diseases. Low-carbohydrate diets like the Atkins Diet are popular for rapid weight loss, but the long-term consequences remain the subject of debate. The Scandinavian low-carbohydrate high-fat (LCHF) diet, which has been popular in Scandinavian countries for about a decade, has very low carbohydrate content (~5 E %) but is rich in fat and includes a high proportion of saturated fatty acids. Here we investigated the metabolic and physiological consequences of a diet with a macronutrient composition similar to the Scandinavian LCHF diet and its effects on the organs, tissues, and metabolism of weight stable mice. Methods Female C57BL/6J mice were iso-energetically pair-fed for 4 weeks with standard chow or a LCHF diet. We measured body composition using echo MRI and the aerobic capacity before and after 2 and 4 weeks on diet. Cardiac function was assessed by echocardiography before and after 4 weeks on diet. The metabolic rate was measured by indirect calorimetry the fourth week of the diet. Mice were sacrificed after 4 weeks and the organ weight, triglyceride levels, and blood chemistry were analyzed, and the expression of key ketogenic, metabolic, hormonal, and inflammation genes were measured in the heart, liver, and adipose tissue depots of the mice using real-time PCR. Results The increase in body weight of mice fed a LCHF diet was similar to that in controls. However, while control mice maintained their body composition throughout the study, LCHF mice gained fat mass at the expense of lean mass after 2 weeks. The LCHF diet increased cardiac triglyceride content, impaired cardiac function, and reduced aerobic capacity. It also induced pronounced alterations in gene expression and substrate metabolism, indicating a unique metabolic state. Conclusions Pair-fed mice eating LCHF increased their percentage of body fat at the expense of lean mass already after 2 weeks, and after 4 weeks the function of the heart deteriorated. These findings highlight the urgent need to investigate the effects of a LCHF diet on health parameters in humans.